Simultaneous observations of irregular sporadic E structures using the LWA and a DPS4D - Obenberger, K. S.; Taylor, C. A.; Colman, J. J.; Dao, E.; Dowell, J.; Eccles, J. V.; Emmons, D. J.; Fallen, C. T.; Holmes, J. M.; Taylor, G. B. (Frontiers in Astronomy and Space Sciences, 2025)
Multi-instrument studies have recently shed new light on the morphology of sporadic E, especially intense sporadic E. Here we present simultaneous observations of dense sporadic E (Es) structures using the Long Wavelength Array (LWA) radio telescopes and a Digisonde Portable Sounder 4D (DPS4D). Our coordinated observations show that the LWA radio telescopes in central New Mexico can reliably locate regions of dense Es structures as they pass over a Digisonde located over 500 km away in Texas. The LWA appears to be most sensitive to the densest Es structures, which also appear to contain irregularities with vertical structure, possibly indicating turbulence. These irregularities cause off-zenith backscatter, as observed by the DPS4D, and are observed to move at speeds of a few tens of m/s. The irregularities also appear to act as a phase screen, producing short-lived daytime spread F and E conditions. We hypothesize that turbulent structures driven by the Kelvin–Helmholtz (KH) instability may be responsible for the observations.